Applying Importance Performance Analysis (IPA) to Measure the Perceived Quality, Perceived Price, Customer Experience on Netflix - Adi, Eri Hartati; Baihaki, Adam Rizki; Wulandari, Ririn (Jurnal Doktor Manajemen (JDM), 2024)
The rapid growth of online streaming services has intensified competition within the industry, compelling providers like Netflix to continually assess and enhance their offerings. This study aims to measure and evaluate the perceived price, perceived quality, and customer experience of Netflix using Importance-Performance Analysis (IPA). By collecting data from a diverse sample of Netflix users, this research identifies the critical areas where Netflix excels and areas requiring improvement. The findings highlight the aspects of the service that are most valued by customers and provide actionable insights for optimizing service strategies to enhance user satisfaction and retention. The results reveal that while Netflix generally performs well in terms of content quality and user experience, certain aspects such as perceived price and specific service features need attention to maintain competitive advantage.